Modeling pesticide use intention in Pakistani farmers using expanded versions of the theory of planned behavior. Issue 3 (16th March 2021) - Khan, Fawad Zafar Ahmad; Manzoor, Syed Amir; Akmal, Muhammad; Imran, Muhammad Usama; Taqi, Muhammad; Manzoor, Syed Asad; Lukac, Martin; Gul, Hafiza Tahira; Joseph, Shimat V.
Abstract: We explore the intentions of farmers' pesticide use by using expanded versions of the theory of planned behavior (TPB). We added variables such as farmers' knowledge about pesticides, moral norms, progressive farming approach, farm size, farming experience, and formal education of the farmers as additional predictors in the original TPB model. We interviewed 390 cotton farmers in Multan and used a hierarchical multiple regression modeling framework to run a series of multiple regression models (based on original and expanded versions of TPB) and found that the expanded TPB models with the addition of, (a) farmers' knowledge of pesticides (R 2 change = 0.089, F change(2, 384) = 24.8, p < 0.01), (b) farmers' progressiveness (R 2 change = 0.037, F change(1, 383) = 21.5, p < 0.01), and (c) socio-economic variables (R 2 change = 0.032, F change(3, 380) = 6.4, p < 0.05) statistically significantly improved the explanatory power of the original TPB model. Farmers' knowledge of pesticides (β = 0.316, t = 6.320, p < 0.01), and progressive farming approach (β = 2.80, t = 5.834, p < 0.01) were the most influential variables determining pesticide use intention. Pesticide use can be optimized through improved extension services, by improving pesticide knowledge and training farmers in new farming practices.